The ultrastructural examination of gingival fibromatosis - (:unkn) unknown (My University, 1994)
Hereditary gingival fibromatosis (GF) is a special type of fibrous overgrowth classified as non-inflammatory gingival enlargement. Microscopically, the connective tissue consists of coarse collagen bundles and fibroblasts. The ultrastructural examination of fibrous gingival hyperplasia reveals that fibroblasts phagocyte the mast cell granules and mast cells stimulate collagen synthesis which results in hyperplasia. In the ultrastructural examination of phenytoin-induced hyperplasia, fibroblasts, phagocytosing mast cell granules were also found. Based on these findings, the purpose of this study is to establish whether there is a relationship between fibroblasts and mast cells in GF. The gingival tissues of 5 patients with GF were examined ultrastructurally. In the connective tissue, well-defined bundles of collagen fibres were found together with fibroblasts and capillaries. There were mast cells around these capillaries which had collapsed lumens. The proximity of the mast cells and fibroblasts may indicate that mast cells play some role on collagen synthesis of fibroblasts.
Keywords: Female; Humans; Male; Gingiva; Biopsy; Fibroblasts; Microscopy, Electron; Connective Tissue; Fibromatosis, Gingival; Mast Cells